2022
DOI: 10.3390/mi13020315
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Applications of Programmable DNA Nanostructures

Abstract: Deoxyribonucleic acid (DNA) nanotechnology, a frontier in biomedical engineering, is an emerging field that has enabled the engineering of molecular-scale DNA materials with applications in biomedicine such as bioimaging, biodetection, and drug delivery over the past decades. The programmability of DNA nanostructures allows the precise engineering of DNA nanocarriers with controllable shapes, sizes, surface chemistries, and functions to deliver therapeutic and functional payloads to target cells with higher ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 165 publications
0
4
0
Order By: Relevance
“…126,127 In addition, the triggered reconfiguration of DNA nanostructures and the control over the optical properties of the systems found extensive applications in intracellular sensing, 128 imaging, 129−131 and therapeutic applications. 132,133 The interaction of light and nucleic acid structures has attracted specific interest. In contrast to the interaction of auxiliary triggers such as pH, chemical agents, enzymes or oligonucleotide fuel/antifuel strands to manipulate DNA structures, all of which alter the composition of the systems by generating waste products, light provides a clean energy source to control the structures and properties of oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…126,127 In addition, the triggered reconfiguration of DNA nanostructures and the control over the optical properties of the systems found extensive applications in intracellular sensing, 128 imaging, 129−131 and therapeutic applications. 132,133 The interaction of light and nucleic acid structures has attracted specific interest. In contrast to the interaction of auxiliary triggers such as pH, chemical agents, enzymes or oligonucleotide fuel/antifuel strands to manipulate DNA structures, all of which alter the composition of the systems by generating waste products, light provides a clean energy source to control the structures and properties of oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the triggered reconfiguration of nucleic acid strands provides versatile means to guide the formation of DNA nanostructures, to control the aggregation/disaggregation of DNA nanoparticles , or to stimulate the oligomerization of DNA scaffolds such as the switchable dimerization/trimerization of origami tiles , or DNA tetrahedra . Diverse applications of reconfigurable DNA structures were suggested, including the development of sensors, gated drug carriers for controlled release, and stimuli-responsive DNA-based materials such as hydrogels revealing controlled stiffness properties, shape memory, self-healing, , and mechanical applications. , In addition, the triggered reconfiguration of DNA nanostructures and the control over the optical properties of the systems found extensive applications in intracellular sensing, imaging, and therapeutic applications. , …”
Section: Introductionmentioning
confidence: 99%
“…For gene-editing applications where cleavage precision is paramount, higher fidelity is first required before the photoresponsive I-TevI nuclease can be fully exploited. The modular I-TevI nuclease is however well suited for in vitro purposes and may have applications for controlling the top-down synthesis of DNA nanostructures for 2D and 3D DNA architectures and microarrays and the release of molecular payloads from DNA-based precursors. , As these applications typically do not require high fidelity, the light-responsive I-TevI nuclease developed here could be applied without further engineering for optical control. In summary, we have demonstrated that monomeric homing endonucleases can be reengineered for optical control with programmable specificity by fusion of independent functional domains to LOV domain photoreceptors with notable dynamic range for a first-generation platform.…”
Section: Discussionmentioning
confidence: 99%
“…Large negatively charged DNA nanotubes could penetrate into the cell even without conjugation with transfection agents, as the authors suggest, due to the thick shell of DNA chains in the structures. However, it is still unknown how DNA nanotubes are taken up by cells [ 263 ].…”
Section: Delivery Of Dna-based Nanomaterialsmentioning
confidence: 99%